Peningkatan Kemampuan Literasi Numerasi Siswa Sekolah Dasar melalui Program Kampus Mengajar 7 - Ansya, Yusron Abda'u; Mailani, Elvi (FONDATIA, 2024)
This study aims to describe the implementation of the Kampus Mengajar 7 in improving literacy and numeracy of elementary school students at UPT SD Negeri 060809 Medan. The research method used was descriptive qualitative involving students, teachers and school officials. Data were collected through observations, interviews, as well as the AKM pre-test and post-test. Analysis was conducted by combining field observations and numerical data to illustrate the impact of the program on improving literacy and numeracy. Based on the AKM post-test, 137 students (76.12%) achieved the good category in literacy, while 143 students (79.45%) showed significant improvement in numeracy. The results show that the Kampus Mengajar 7 program plays a significant role in helping to improve the quality of basic education, particularly in students' literacy and numeracy skills.